Education and inequality in india : a classroom view - Majumdar, Manabi; Mooij, Jos E. (London : Routledge, 2011)
'This book focuses on primary education in India and interrogates what schooling means and does to children from weaker sections of Indian society and which values underpin the school system. It examines whether the concept of'education for all' is just a mechanically conceived policy target to chasing enrolment and attendance or whether it a larger social goal and a deeper political statement about the need for attacking entrenched social inequalities, and above all an affirmation of the idea that schooling has a liberating potential. Drawing on original data collected in the two states of Andhra Pradesh and West Bengal, the authors first present the multiple ways in which social class impinges on the educational system, educational processes and educational outcomes. In the second part of the book, issues around autonomy and accountability are explored via an analysis of the position of teachers within the educational hierarchy, and by looking at the various possibilities of making teachers accountable. The last part centres on the learning process, with a particular focus on the classroom. The conclusion includes recommendations that are related to the necessity for a larger debate and normative framework, which includes private schools as possible partners in the pursuing of a public good for which a public entity should take some responsibility, and in conjuncture to that, the necessity to move from government action and responsibilities to a broader concept of public action'-- Provided by publisher.
'Universalization of primary education has been high on the policy agenda in India. This book looks at the reproduction of social inequalities within the educational system in India, and how this is contested in different ways. It examines whether the concept of education for all' is just a mechanically conceived policy target to chasing enrolment and attendance or whether it is a larger social goal and a deeper political statement about the need for attacking entrenched social inequalities. Drawing on original data collected in the two states of Andhra Pradesh and West Bengal, the authors present the multiple ways in which social class impinges on the educational system, educational processes and educational outcomes. The book goes on to explore issues around autonomy and accountability via an analysis of the position of teachers within the educational hierarchy, and by looking at the various possibilities of making teachers accountable. Recommendations related to the necessity for a larger debate and normative framework are made, including whether private schools should play a role, and whether it is necessary to move from government action and responsibilities to a broader concept of public action. The book presents in interesting contribution for students and scholars of South Asian studies, as well as Education and Public Policy studies'-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Educational equalization -- India; Education, Elementary -- India; Equality -- India